POSTPARTUM 'S KNOWLEDGE ABOUT BREAST CARE AS EXCLUSIVE EFFORTS AT RS ST ELISABETH, BATAM CITY - Sarita Miguna; Magfirah Al’amri (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2021)
Background : The puerperium is a recovery period after the birth process begins at the birth of the placenta, and ends when the reproductive organs return to normal, such as in a woman who is not pregnant. An effort is needed to increase milk production during the puerperium, one of which is breast care so that the rights of babies to get breast milk from their mothers are fulfilled. The purpose of this study was to determine the knowledge of postpartum mothers about breast care. Method : The research method used is descriptive, conducted at the hospital. ST Elisabeth Batam City, the research was conducted for 6 months, the population in this study were all postpartum mothers who were in the postpartum room of Elisabeth Hospital Batam City when the research took place, namely as many as 33 people, the sampling technique was carried out by using total sampling technique with research instruments using a questionnaire. Result : The results showed that the majority of good knowledge as many as 24 people (72.7%) and less knowledgeable as many as 9 people (27.3%). conclusion : The conclusion of this study most of the knowledge of postpartum mothers about breast care is Good. Suggestions for respondents to apply breast care properly in order to be able to provide breastfeeding exclusively